Self-organized criticality in a mesoscopic model of excitatory-inhibitory neuronal populations by short-term and long-term synaptic plasticity - Ehsani, Masud; Jost, Jürgen (Frontiers in Computational Neuroscience, 2022)
In \cite{Ehsani22}, we have shown that the dynamics of an interconnected population of excitatory and inhibitory spiking neurons wandering around a Bogdanov-Takens (BT) bifurcation point can generate the observed scale-free avalanches at the population level and the highly variable spike patterns of individual neurons. These characteristics match experimental findings for spontaneous intrinsic activity in the brain. In this paper, we address the mechanisms causing the system to get and remain near the BT point. We show how the network tunes itself through local long-term synaptic plasticity by STDP and short-term synaptic depression to wander around this bifurcation point. We propose an effective stochastic neural field model which captures the dynamics of the network in the vicinity of the BT point. The mesoscopic model that we derive matches the directed percolation model at the absorbing state phase transition.